2010
DOI: 10.1002/jcp.22391
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces apoptosis of human nasopharyngeal carcinoma cells via activation of multiple apoptotic pathways

Abstract: Resveratrol, a naturally occurring dietary compound with chemopreventive properties has been reported to trigger a variety of cancer cell types to apoptosis. Whether resveratrol shows any activity on human nasopharyngeal carcinoma (NPC) cells remained to be determined. The aim of this study was to investigate the effect and mechanism of resveratrol on human NPC cells. Treatment of resveratrol resulted in significant decrease in cell viability of NPC cell lines in a dose- and time-dependent manner. A dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 51 publications
5
23
0
Order By: Relevance
“…It seems that MCL-induced mitochondrial damage seems to be the cause rather than the effect of MCL-induced cell death because the phenomenon was detectable as early as 3 hours after treatment (data not shown). These results agree with the prevailing response of most cancer cells exposed to chemotherapeutic components (7,16,39).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It seems that MCL-induced mitochondrial damage seems to be the cause rather than the effect of MCL-induced cell death because the phenomenon was detectable as early as 3 hours after treatment (data not shown). These results agree with the prevailing response of most cancer cells exposed to chemotherapeutic components (7,16,39).…”
Section: Discussionsupporting
confidence: 90%
“…Apoptosis is executed by caspases and caspase-3 is a key protease associated with DNA fragmentation and apoptosis (39). Two main pathways have been involved in activation of caspase-3, including the caspase-8-regulated plasma membrane extrinsic pathway and the caspase-9-regulated cell damage intrinsic pathway (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only three in vitro studies have suggested the potential inhibitory effects of resveratrol on human NPC cells (33)(34)(35). The underlying molecular mechanisms remain largely unknown, and there is also a lack of in vivo evidence to support the anticancer activity in human NPC.…”
Section: Discussionmentioning
confidence: 99%